Prevalence of Musculoskeletal Disorders and their Associated Risk Factors among Computer Users - Amer, Shadi; Yamin, Dina; Hamzah, Nurul Ainun; Mohd Nawi, Mohd Nazhari; Mamat, Mohd Noor; Mohd Nawi, Mohd Nasrom (Universitas Airlangga, 2025)
Introduction: In 21st century, computers are crucial devices in universities’ official operations. In academic institutions, musculoskeletal disorders (MSDs) are leading causes of decreased productivity, absenteeism, disability, and illness. Office staff who use computers extensively are vulnerable to occupational MSDs. This study aims to determine risk factors of MSDs among computer users in a public university. Methods: This cross-sectional study involved 320 respondents among computer users working in all departments in Universiti Sains Malaysia Health Campus using random sampling. Tools used were a self-administered questionnaire containing questions on socio-demographical data, Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) for assessing musculoskeletal disorder and observation and Rapid Office Strain Assessment (ROSA) to assess office equipment and quantify exposure to risk factors in office work environment. Results: Response rate was 92% and 86.2% of respondents reported work-related musculoskeletal disorders (WRMSDs). The most prevalent MSD was lower back, 62.8% of MSD cases, followed by right shoulder (53.4%), hip/buttock (46.4%), and left shoulder (45.3%).Older age was significantly associated with WRMSDs (OR=6.944, CI:1.238-39.017, p=0.0.028) and with neck MSDs (OR=3.908, CI:1.342-11.377, p=0.012), while female gender was significantly associated with neck MSDs (OR=2.042, CI:1.199-3.475, p=0.009) and with upper arm MSDs (OR=1.791, CI:1.091-2.941, p=0.021). Older age was significantly associated with upper arm MSDs (OR=3.303, CI:1.006-10.849, p=0.049), while those with healthy and overweight were significantly associated with upper arm MSDs (OR=0.092, CI:0.010-0.814, p=0.046), (OR=0.127, CI:0.014-1.123, p=0.032), respectively. Conclusion: The prevalence of reported WRMSDs and MSDs at neck and upper arm were associated with socio-demographic background and high duration of computer use; 12.2% of workstation presented musculoskeletal discomfort risk.